A-signifying Semiotics - Genosko, Gary (Public Journal of Semiotics, 2008)
This paper offers an interpretation of the theory of a-signifying semiotics developed by French intellectual-activist Félix Guattari in the 1970s. The argument is that these types of part-signs are perfectly adapted to the quasiautomated networks of contemporary infocapitalism, and their characteristics are studied with regard to the magnetic stripe on a plastic bank or credit card. Although these part-signs are akin to signals since they do not have a semantic dimension, they do have a political materiality in the technologies, that is, the information strands of the machinic phylum, in which they are found. This technomaterialist semiotics of infocapital places Guattari at the forefront of innovative semiotic theory.